Vaccine hesitancy: A serious threat to global health. (2nd March 2019) - Hancock, David
Abstract : There is a growing phenomenon of reluctance or refusal by families to have their children vaccinated against childhood diseases. David Hancock looks at what vaccine hesitancy might mean for the future health of populations in the UK and worldwide